I share, therefore i am? The (re) construction of consumer identity by collaborative con-sumption - Andrade, Helena da Gama Cerqueira; Pinto, Marcelo de Rezende; de Almeida, Gustavo Tomaz; Mesquita, Maytê Cabral (REBRAE, 2017)
This article aims to investigate how the practice of collaborative consumption, which privileges the "use" in detriment of "possessions" of goods, influences the construction, reconstruction and deconstruction of consumer identity. The practice of coworking was chosen as a means to conduct the research. The study was theoretically based on the themes: culture and consumption, collaborative consumption, coworking and identity. Using a qualitative, ethnographic methodology, the study focused on people who use coworking to work, and sought to identify and analyze aspects related to their consumption habits and identity traits. The study collected the data through participant observations and in-depth interviews, producing results that enabled the articulation with the CCT - Consumer Culture Theory. It was found that the collaborative consumption is part of the social and cultural universe of this group of consumers to the extent that, in addition to coworking, this is an environment that presupposes collaboration. The fact that they are working in this environment and living with other people in the same situation, makes this climate of collaboration extrapolate the walls of coworking and influence them in order to adopt other attitudes and collaborative habits, which shows a relationship between consumption and identity.